The Influence of Promotions and Prices on Purchase Decisions in the Shopee Application Marketplace (Case Study on STIMI Banjarmasin Students) - Rizki Aprianor; Titien Agustina; Sampurnawati (PT. Hanken Sukses Jaya, 2026)
The purpose of this study is to find out the extent of the influence of promotions and prices on purchase decisions in the Shopee application marketplace (Case Study on STIMI Banjarmasin Students). Dependent variables (promotion and price) while independent variables (purchase decisions). This type of research is quantitative research. The number of populations in this study is students of the S1 management study program of STIMI Banjarmasin regular morning class. Sample selection using the slovin formula and producing 60 samples. The data collection technique used questionnaires. The sampling technique uses random sampling. Based on the results of the study with the statistical calculation of partial tests (t-test) Promotions have a partial effect on Purchase Decisions in the Shopee application marketplace (Case Study on STIMI Banjarmasin Students) and Price Partially Affect Purchase Decisions in the Shopee Application Marketplace (Case Study on STIMI Banjarmasin Students). Simultaneously, Promotion and Price affect Purchase Decisions in the Shopee application marketplace (Case Study on STIMI Banjarmasin Students).